Catalytic fluorination of HCFC-133a (1,1,1-trifluoro-2-chloroethane) - Cho, D.H.; Kim, Y.G.; Chung, M.J.; Chung, J.S. (Korean Institute of Chemical Engineers, 1997)
Catalytic fluorination of HCFC-133a was performed over metal oxide catalysts. Chromium oxide showed the best catalytic activity among several metal oxides tested. An increase in the crystallinity with decreased surface area resulted in a decrease of catalytic activity for the fluorination reaction. Active phase of chromia is Cr-O-F-OH having a proper ratio of O/F and a high hydroxyl content. The hydroxyl content on the catalyst is strongly dependent on support material. The selectivity to HFC-134a is independent of the O/F ratio on the Cr surface.